132k views
6 votes
Help me asap!!!!

Consider the function, y= 2x – 1
use the above function to complete the following table.

Help me asap!!!! Consider the function, y= 2x – 1 use the above function to complete-example-1
User Ismet
by
5.6k points

1 Answer

3 votes

Answer (numbers needed in boxes, going from top to bottom):

1

-1

-3

3

Explanation:

f(x) is another way of saying y. So, the table is asking, "when substituting these x values for the x's in the function, what does y equal?" So, to answer the question, substitute each x value into the equation and solve.

1) Start with the x value of 1. Substitute 1 for x in y = 2x - 1 and solve:


y = 2(1)-1\\y = 2 - 1\\y = 1\\

So, when x equals 1, y equals 1. Therefore, the first box on the top must be filled out with the number 1.

2) Do the same with the rest of the x values. Here are the steps to solve each one, going in order from the top towards the bottom:

x = 0


y = 2(0) - 1\\y = 0 - 1\\y = -1

x = -1


y = 2(-1) - 1\\y = -2 -1 \\y = -3\\

x = 2


y = 2(2)-1\\y = 4-1\\y = 3\\

User RAmAnA
by
5.4k points